PENGARUH HEDONIC SHOPPING MOTIVATION DAN SALES PROMOTION TERHADAP IMPULSE BUYING MELALUI POSITIVE EMOTION SEBAGAI VARIABEL MEDIASI - Ana Latifa; Endah Pri Ariningsih; Dedi Runanto (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study aims to analyze the effect of hedonic shopping motivation and sales promotion on impulse buying with positive emotion as a mediating variable among visitors of Armada Town Square Mall Magelang. This research uses a quantitative approach with a survey method through questionnaires distributed to 150 respondents selected using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with SmartPLS 4.1.1.6 software. The results show that hedonic shopping motivation and sales promotion have a positive and significant effect on impulse buying. In addition, both variables also have a positive and significant effect on positive emotion. Positive emotion is found to have a positive and significant effect on impulse buying. Furthermore, positive emotion is proven to mediate the relationship between hedonic shopping motivation and sales promotion toward impulse buying. These findings indicate that consumers’ positive emotions play an important role in strengthening impulsive buying behavior triggered by hedonic motivation and sales promotions. This study contributes theoretically to the development of the Stimulus–Organism–Response (S–O–R) model and enriches consumer behavior literature in the retail context. Practically, the findings can be used by shopping mall managers and tenants to design marketing strategies that create positive emotional experiences to enhance consumers’ impulse buying behavior.